PRODUCTION OF DUCTILE CAST IRON BY RECYCLING GRAY CAST IRON SCRAP WITH ADDING VARIOUS LOCAL MATERIALS - A. Mnati, Ali; K. Resan , Kadhim (Journal of Engineering and Sustainable Development, 2023)
Ductile cast iron is also called spheroidal graphite cast iron or nodular cast iron. It contains graphite in the semblance of nodules. Automobile scrap (i.e., the engine block) made from gray cast iron was used in this study. In this paper, the recycling of gray cast iron to ductile iron, and its influence on the microstructure and mechanical characteristics be studied. Four kilograms of scrap were put in a crucible and then heated up to 1400°C in an oil-fired crucible furnace. For desulfurization, 4% burnt lime with 0.5% fluorspar was direct tapped into the melt at 1400°C. Then, the additions were 3.5% nickel, 0.75% Ferro molybdenum, and 0.5% Ferro manganese of the scrap weighing. Also, 3.75% nodularizing alloy and 1% inoculating alloy of scrap weight were to treat the molten at 1450°C. Samples analyses have been achieved to determine their composition, tensile strength, impact strength, Brinell hardness, and microstructural. The microstructures revealed that the scrap sample possesses flake graphite, and the produced sample includes nodule graphite. It is observed that the ultimate tensile stress, elongation, and hardness of the scrap sample, which are 247.75 MPa, 6%, and 400.3 HB, respectively, increased in the product sample to 416.23 MPa, 8%, and 451 HB, respectively.